Economic evaluation of a vision-based patient monitoring and management system in an acute adult and an older adult mental health hospital in England. (31st December 2022) - Malcolm, Robert; Shore, Judith; Stainthorpe, Angela; Ndebele, Faith; Wright, Kay
Abstract: Background and aims: Patients on acute adult and older adult inpatient mental health wards are at an increased risk of accidental injuries and deliberate harm to self and others. A vision-based patient monitoring and management (VBPMM) system was designed by Oxehealth Limited to support ward staff to provide better and more efficient care and to reduce incidents. The VBPMM system uses an infrared-sensitive camera, installed in a patient's room, that works with cleared medical device software to deliver contact-free vital sign and activity insights to clinical teams. Data from two studies undertaken at an English National Health Service (NHS) mental health trust were used to inform an early economic assessment of VBPMM implementation into acute adult and older adult mental health wards. Methods: A cost calculator was used to compare the introduction of the VBPMM system as an adjunct to standard care versus standard care alone. Observational data were collected at two English NHS mental health trusts. Both compared data pre- and post-VBPMM implementation using a 12-month baseline period. The model estimated cost per occupied bed day, cost per patient, annual cost per average-sized ward, and total cost to NHS mental health trusts across England. Costs were modeled from an NHS perspective over a 12-month time horizon. Scenario analysis was conducted to test the uncertainty of results using statistical significance of key inputs. Results and conclusions: This early analysis indicated that the VBPMM system is likely to be cost saving within both settings examined, with an estimated cost saving of £272 per acute adult mental health patient and £4, 591 per older adult mental health patient. This translates to £22.3 and £63.3 million, respectively, across NHS mental health trusts in England every year. VBPMM, therefore, has the potential to augment standard care, leading to positive clinical outcomes and monetary savings.